STUDY OF LIPID PROFILE AND ATHEROGENIC INDEX IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - FATIMA, DURAIN; TIWARI, SURYA; GOWARDIPE, PRAVIN S; SK, SADAWARTE (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The present study’s design investigated the lipid parameters level and atherogenic index in atherosclerosis and cardiovascular disease risk development in chronic obstructive pulmonary disease patients. Methods: The study consists of 108 clinically diagnosed and confirmed spirometry-stable chronic obstructive pulmonary disease (COPD) patients (Mild, Moderate, and Severe), and the controls were 36 healthy individuals of the same age and sex. Blood samples were collected and the lipid profile was done. The atherogenic index of all COPD patients was calculated using the values of lipid parameters. Results: The observation revealed that as compared to the control group, total cholesterol, triglycerides, low-density lipoproteins (LDL), and very LDLs were significantly (p<0.001) raised in all the COPD sub-groups, and high-density lipoproteins levels showed significantly (p<0.001) decreasing levels in all COPD groups as compared to controls. The COPD sub-group has a higher atherogenic risk (p<0.001) than controls. Conclusion: In COPD patients with dyslipidemia, there is an increased atherogenic risk, which predicts future cardiovascular risk.